Low-Stiffness Hydrogels Promote Peripheral Nerve Regeneration Through the Rapid Release of Exosomes - Liu, Zhixiao; Tong, Hua; Li, Jian; Wang, Ling; Fan, Xiaoyi; Song, Honghao; Yang, Mei; Wang, Haowei; Jiang, Xin; Zhou, Xuhui; Yuan, Hongbin; Wang, Yue (Frontiers in Bioengineering and Biotechnology, 2022)
A hydrogel system loaded with mesenchymal stem cell-derived exosomes (MSC-Exos) is an attractive new tool for tissue regeneration. However, the effect of the stiffness of exosome-loaded hydrogels on tissue regeneration is unclear. Here, the role of exosome-loaded hydrogel stiffness during the regeneration of injured nerves was assessed in vivo. The results showed that the photocrosslinkable hyaluronic acid methacrylate hydrogel stiffness plays an important role in repairing nerve injury. Compared with stiff hydrogels loaded with exosomes, soft hydrogels loaded with exosomes showed better repair of injured peripheral nerves. The soft hydrogel promoted nerve repair by quickly releasing exosomes to inhibit the infiltration of macrophages and the expression of the proinflammatory factors IL-1β and TNFα in injured nerves. Our work revealed that exosome-loaded hydrogel stiffness plays an important role in tissue regeneration by regulating exosome release behavior and provided important clues for the clinical application of biological scaffold materials.